Perkembangan Populasi Ternak Besar Dan Unggas Pada Kawasan Agribisnis Peternakan Di Sumatera Barat - W Sartika; E Rahmi (Universitas Andalas, 2012)
This study was conducted to look at developing of ruminant and poultry population in agribusiness area in West Sumatra . The research method was used a literature study of farm statistics in 2011. Data analysis was done by descriptive qualitative agribusiness areas in West Sumatra with livestock population data Regency/City in West Sumatra 2011 and the results were depicted through graphs . The results showed that the area of agribusiness farms that had been established by the government of West Sumatra there were several areas of the district / city that was also the potential to served the agribusiness area not included in the region and vice versa. West Sumatra province had considerable potential for the development of both ruminant and poultry. Ruminant such as beef cattle was very good to be developed in the Pesisir Selatan, Padang Pariaman and 50 Kota with a population of respectively 23 % and 10 % of the total cattle population was in West Sumatra. Buffalo potential to be developed in Agam, Padang Pariaman, and Sijunjung . Types of poultry chicken laying and broiler with the largest number of population was 5,867,890 and 4,796,490 tails tails were in Limapuluh Kota which was the production center for the cattle.